A review on oral herbal drugs affecting chloasma based on Persian Medicine and Conventional Medicine - Marjan Mahjour; Mandana Tavakkoli Kakhki; Zohre Feyzabadi (Mashhad University of Medical Sciences, 2019)
Introduction: Due to the prevalence of melasma pregnancy (chloasma) and tendency to complementary medicine, this review study was performed with aim to introduce the medicinal herbs affecting the prevention and treatment of chloasma. Methods: This review study was performed by searching in 10 authentic books of Persian medicine with the "Introducing a model for prioritization of drugs, based on Iranian Traditional Medicine references" model and also 32 valuable articles with searching in ISI, Scopus, PubMed, Magiran & SID by using the inclusion criteria of available books and articles with the keywords of Kalaf (melasma and chloasma) in Persian medicine and also chloasma and herbal drug in conventional medicine from 1978-2018. The results were compared. Results: Based on the findings of this study, chloasma has been discussed in detail in Persian and conventional medicine. Persian scholars considered oligomenorrhea as the cause of chloasma. They had recommended treatments such as lifestyle and nutrition modifications, the use of herbal drugs and the use of manual therapies. Accordingly, the use of Crocus sativus, Allium ampeloprasum, Fumaria officinalis, Vitis vinifera, Ficus carica, Trigonella foenum graceum, Apium graveolens and Cicer arietinum was prescribed for treatment of chloasma. Nowadays, conventional medicine has proved the its various mechanisms such as having antioxidants and multivitamins and confirmed its effectiveness for treatment of melasma. Conclusion: Based on the proven mechanism of the plants affecting chloasma, the use of these foods in the diet of patients along with conventional medicine will help to improve the disease faster.